Comment on "Efficacy of ginseng and its ingredients as adjuvants to chemotherapy in non-small cell lung cancer" by H. Zhu, H. Liu, J. H. Zhu, S. Y. Wang, S. S. Zhou, M. Kong, Q. Mao, F. Long, Z. J. Fang and S.-L. Li, Food Funct., 2021, 12, 2225. Issue 15 (14th July 2022) - Lee, Hye Won; Ang, Lin; Lee, Myeong Soo
Abstract : This comment raises concerns about the article "Efficacy of ginseng and its ingredients as adjuvants to chemotherapy in non-small cell lung cancer".